Genomic and phylogenetic analysis of hepatitis C virus isolates from Argentine patients: A six-year retrospective study - Quarleri, Jorge Fabian (2000)
Typing of hepatitis C virus (HCV) isolates from Argentine patients was performed by using different methodologies in a population of 243 patients. HCV subtype was assigned based upon restriction fragment length polymorphism (RFLP). HCV RNA genomes obtained from serum samples were classified as belonging to clade 1 (53.5%), 2 (23.0%), or 3 (8.6%); 14.8% of samples showed HCV mixed infections, more frequently implying different subtypes within the same clade. In addition to RFLP typing, phylogenetic relatedness among sequences from both 5′ untranslated region (n = 50) and nonstructural 5B coding region (n = 15) was established.